Self reported physical activity, public health, and perceived environment: results from a comparative European study. Issue 2 (1st February 2001) - Rütten, A; Abel, T; Kannas, L; von Lengerke, T; Lüschen, G; Diaz, J A Rodríguez; Vinck, J; van der Zee, J
Abstract : STUDY OBJECTIVE: The focus of physical activity promotion is moving from methods for increasing health enhancing physical activity on the individual level to higher level strategies including environmental and policy approaches. Scientific inquiry, traditionally related to individual-based strategies, requires adaptation and refinement when environmental and policy changes become more relevant. The objective of this study is to investigate the significance for behaviour and health of community-based environments that encourage physical activity. DESIGN AND SETTING: The article presents data and results from a cross sectional comparative survey of the general population in six European countries (Belgium, Finland, Germany (East and West), Netherlands, Spain, Switzerland). Specifically, the relation between perceived community-based opportunities for physical activity, self reported physical activity, and self rated health status is investigated. PARTICIPANTS: Representative samples of general populations (adults 18 years or older). Overall response rate: 53.5%. Sample sizes realised: Belgium: n = 389; Finland: n = 400; Germany (East): n = 913; Germany (West): n = 489; Netherlands: n = 366; Spain: n = 380; Switzerland: n =406. MAIN RESULTS: Analyses show that best opportunities are reported by people who are lightly to moderately physically active. People's self rated health is moderately, but significantly associated with both perceived opportunities, and physical activity itself. These predictors interact in that especially for women, the health impact of physical activity is more pronounced in case of good opportunities. CONCLUSIONS: The paper shows the potential of opportunities within residential and community environments with regard to physical activity, both for behaviour and health. Opportunities may enable the population, especially women, to develop an active lifestyle, and thus improve their health. Future studies with objective indicators for physical activity related environments should test the findings that are based on perceptions.